(untitled) (Research, Society and Development, 2024)
Developmental dysplasia of the hip (DDH) is one of the most common orthopedic anomalies and is characterized by a wide spectrum of pathologies, from minor laxity of the ligaments in the hip joint to complete dislocation. Risk factors for this condition include the female sex, left side, breech birth and the genetic component. However, other risk factors that are not as defined as the first child are the focus of discussion. This article is configured as an integrative literature review. It used scientific materials published online by entities linked to scientific research. Among the review methods, the present study opted for the integrative modality. Data collection was carried out between January and March 2024 and primary works published between 2000 and 2023 were selected and the following question was guided: “Do first born children have a higher risk of developmental dysplasia of the hip? An integrative review” The objective of the article was to analyze whether being the first child is a risk factor for developmental dysplasia of the hip. The work demonstrated a higher prevalence in the literature stating that being a firstborn is a risk factor for DDH. However, more studies are needed to verify whether firstborn status is simultaneous with other risks and to try to estimate whether firstborn status is an isolated risk factor.